PERJANJIAN SEWA MENYEWA TANAH UNTUK JALAN ANTARA PT. CIPTA MARGA PERKASA DENGAN PEMILIK TANAH DI KECAMATAN RANTAU PANDAN KABUPATEN BUNGO - Abdul Hariss (Universitas Batanghari Jambi, 2015)
Land lease agreements are not only done by individuals, but also done by an agency or legal entity with legal entities or between legal entities with those individuals, such as including PT Cipta Perkasa Clan who held a lease agreement rent land with land owners or residents of the subdistrict Rantau Pandan Bungo. PT Cipta Perkasa Clan held a lease agreement with the landlord rented land is to organize a way to place his efforts.After the existence of the bonding agreement renting the land for the procurement of road to the place of business between PT. Cipta Perkasa Clan with the landowner, the rights and obligations for each party, the rights at one party an obligation on behalf of the other and vice versa. The parties committing yourself in the land lease agreement are not allowed to perform inkar promise (tort), but in reality, not a possibility the existence of the tort, both deeds committed by either party or by both parties.The existence of the tort in an agreement, did not escape from the presence of a obstacles faced in the implementation of the land lease agreement itself. If the constraints encountered were not corrected immediately, it is not impossible in addition to violating the agreed contents of the Treaty, may also violate the provisions of the applicable legislation. For it needs immediate relief efforts.Keywords: Tenancy, Land